A Chance at Birth: An Academic Development Activity To Promote Deep Reflection on Social Inequities - Bryan M. Dewsbury (American Society for Microbiology, 2020)
I describe the structure and implementation of an activity I use in academic development, aimed at introducing higher education faculty to social inequities in a profound way. The activity is structured such that previously naïve practitioners as well as those somewhat engaged in equity pedagogies are provided new ways of thinking about the role classroom practices play in social inclusion. Here I reflect on the activity’s genesis, provide suggestions for its use, and present considerations for academic developers interested in using it for their own practice.